On the measurement of the surface pressure in Langmuir films with finite shear elasticity - Aumaitre, E; Vella, D; Cicuta, P (2011)
We investigate the use of the Wilhelmy plate method to measure the surface pressure in a solid-like Langmuir film under compression. Layers of the protein hydrophobin, which exhibits a high shear elastic modulus, are spread and compressed in a Langmuir trough. The resulting isotherms are classified according to the surface pressure and distance between the barriers measured at the onset of buckling. We find that the surface pressure measured in the centre of the layer at the onset of buckling decays with increasing distance between the barriers (which can be tuned by varying the amount of material spread initially). However, unlike the case of particle rafts, the length scale of this decay is not controlled by the width of the trough but rather by the size of the Wilhelmy plate used. We use experiments and a computational model to suggest that this independence of trough width may be attributed to the localised nature of the effect of the trough walls. Our work highlights the potential pitfalls of using the Wilhelmy method to characterize layers with high shear rigidity and may lead to a better understanding of the use of the Wilhlemy plate to measure the surface stress tensor. © 2011 The Royal Society of Chemistry.